PERANCANGAN CONTROL SYSTEM PENGISIAN FLUIDA OTOMATIS MENGGUNAKAN SENSOR ULTRASONIC SEBAGAI LEVEL AIR & SENSOR FLOW INDIKASI ALIRAN AIR BERBASIS IOT - surya Atmajaya; aswadul fitri saiful rahman; a asni b (Lembaga Penelitian Universitas Balikpapan, 2019)
The technology applied in some small and medium businesses still applies conventional processes so that the effectiveness of production is less than optimal, on the other hand the technology develops rapidly, especially industrial automation, for example conventional activities where an officer has to monitor and record every water level held in reservoir / tank, this activity can be replaced by an electronic system, which automatically carries out monitoring by reading parameters on the sensor. By creating an automatic reservoir fluid filling system and ESP 8266 based fluid level monitoring integrated with internet network and LCD Touchscreen to facilitate the operator in monitoring fluid levels in the reservoir and fluid filling automatically